Model Pendekatan Masyarakat Muslim Terhadap Konflik Beragama - Yasin, Muhammad (CV. Creative Tugu Pena, 2024)
This article explains the models of approaches taken by Muslim communities in addressing religious conflicts. There are two approaches among Muslims: a closed-minded approach and an open-minded approach. The former thinks that there is no need to respond to changing situations, while the latter thinks that understanding and interpretation of Islam needs to change depending on the time and situation. In other words, understanding Islam requires other knowledge to make Islam more applicable, socialised and cultured. These two approaches have resulted in the classification of Muslim communities, including Puritan, Moderate and Cosmopolitan Muslim communities. Puritan is someone who has absolutist thinking and demands clarity in interpreting the text. Moderates are people who avoid extreme behaviours and expressions. While cosmopolitan is a person who has an international or global outlook or attitude.